Ladybug girl and the bug squad - Soman, David (Dial Books for Young Readers, 2011)
This book was a Jumpstart Read for the Record Book. The Bug Squad – Bumblebee Boy, Dragonfly Girl, and Butterfly Girl – are coming to Lulu’s house for a play date and she know exactly what they are going to do all day. They use their big imaginations to create their own fun games right in Lulu’s backyard. But when some things don’t go just the way Lulu planned, Dragonfly Girl’s feelings get hurt. This is a job for Ladybug Girl! When Lulu is Ladybug Girl, she knows that even if it isn’t easy, it is important to apologize.